1999
DOI: 10.1080/j.1600-0412.1999.780520.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological factors influencing pelvic lymph node metastases in two ormore sites in patients with cervical carcinoma undergoing radical hysterectomy

Abstract: From these results, patients having these three histopathological parameters could be considered as those with extensive disease distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 12 publications
1
20
1
Order By: Relevance
“…In previous studies, patients with endometrial extension have been shown to have a poor prognosis because of a higher rate of development of distant metastases, [2][3][4][5]18 but there was no explanation of this finding. Narayan et al has shown a correlation between magnetic resonance imaging (MRI) endometrial extension and FDG-PET-detected lymph nodes.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In previous studies, patients with endometrial extension have been shown to have a poor prognosis because of a higher rate of development of distant metastases, [2][3][4][5]18 but there was no explanation of this finding. Narayan et al has shown a correlation between magnetic resonance imaging (MRI) endometrial extension and FDG-PET-detected lymph nodes.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, we suggest that endometrial extension is correlated with lymph node metastases, which correlates with development of distant metastases and a worse prognosis. [2][3][4][5]18 In the absence of FDG-PET evaluation, evidence of endometrial extension may assist in assessing a patient-s risk of lymph node metastasis. This prognostic information may be useful in stratifying patients for risk-adjusted therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological specimens were analyzed by the same pathologists according to the recommendations of the American Society of Pathologists 23 . Clinical-pathologic characteristics, such as tumor size, differentiation grade, lymphatic vascular space invasion (LVSI), parametrial involvement and pelvic lymph node status, were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The pathological specimens were analyzed by the same pathologists according to the recommendations of the American Society of Pathologists [9] . All histological slides were examined after hematoxylin and eosin staining.…”
Section: Methodsmentioning
confidence: 99%